Global ex situ Conservation of Palms: Living Treasures for Research and Education - Griffith, M. Patrick; Meyer, Abby; Grinage, Ayress (Frontiers in Forests and Global Change, 2021)
Under the old taxon Principes, palms were once the Princes of the Kingdom Plantae. First on Engler’s list, they occupy a cherished place to botanists, and remain treasured centerpieces of many gardens. In turn, botanic gardens have put forward a decades-long effort to conserve these widely admired plants, keeping a number of palm species from extinction. Living palm collections also have critical value for comparative ecological studies. In this paper we highlight successful ex situ conservation programs for palms, review how the promising new field of collections genetics can guide ex situ conservation of palms, conduct a family-wide gap analysis for living collections in the Arecaceae, and provide an in-depth case study of ex situ conservation of the genus Sabal. These analyses highlight ways in which gardens can advance palm conservation following four recommendations: collect, cultivate, communicate, and collaborate.